Implementation of Portable Foot and Mouth Disease Inference System Using a Smartphone - Deok Kweon, Ki; Rack Park, Koo; Young Jung, Jin; Jin Cho, Han (International Journal of Engineering and Technology, 2018)
Background/Objectives: Damage has been caused by foot and mouth disease worldwide. The vaccine is used for prevention, but it is difficult because of the variant virus and lack of vaccine. In this paper, we have implemented a system to prevent the expand of foot - and mouth disease in the early onset stage.Methods/Statistical analysis: In order to solve the disadvantages of the fixed-type thermal imaging camera, a smartphone is used to check the temperature of the livestock hoof using an external thermal imaging camera and notify the farmer when the temperature exceeds 34.4 degrees.Findings: The sample livestock was selected as cows and pigs belonging to two-split hooves, and the livestock was deduced from the normal livestock and foot-and-mouth disease, and the result message was sent to the farm owner and the nearby farmer. It is difficult and the accuracy lacks to figure out with a fixed-type thermal imaging camera in a group-raised environment by shooting the hooves and check the temperature and determine which livestock is suspected of foot-and-mouth disease.Improvements: Smartphone-based shooting can be instantly confirmed by the farmer in any environment, and the captured results are collected as Big Data and provided by FCM push alarm function of Android so that it can be recognized on other farms.Â Â